2019
DOI: 10.1088/2631-8695/ab2609
|View full text |Cite
|
Sign up to set email alerts
|

Recycled HDPE reinforced Al2O3 and SiC three dimensional printed patterns for sandwich composite material

Abstract: In the present work, a sacrificial patterns (SP) for investment casting (IC) were prepared with three dimensional (3D) printing (by using fused deposition modelling (FDM) setup) from recycled high density polyethylene (HDPE) recovered from domestic waste reinforced with Al 2 O 3 and SiC particles in different proportions. These SP were further used for preparation of sandwich composite material (SCM) as a novel process. Finally casted functional prototypes as SCM were investigated for surface hardness, porosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The improvement in mechanical properties of 1°recycled thermoplastic material after TSE is certainly useful for enhancing the reusability/ recyclability of the polymers. These results are in line with the observations made by other investigators [21][22][23][24][25][26][27].…”
Section: Mechanical Testingsupporting
confidence: 93%
“…The improvement in mechanical properties of 1°recycled thermoplastic material after TSE is certainly useful for enhancing the reusability/ recyclability of the polymers. These results are in line with the observations made by other investigators [21][22][23][24][25][26][27].…”
Section: Mechanical Testingsupporting
confidence: 93%
“…However, it should be pointed out that the reported FDM [63] was not a real ceramic since the amount of ceramic added was small and there was even no sintering process. Masuda et al [64] also successfully mixed water-soluble resole phenolic resin with SiC ceramic particles to prepare polymer-ceramic wires.…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
“…Singh et al [63] mixed Al 2 O 3 and SiC ceramic particles with high-density waste recycled polyethylene, and formed into polymer-ceramic wires (as shown in Fig. 17(a)).…”
Section: Fused Deposition Modeling (Fdm)mentioning
confidence: 99%
“…The results found that the developed composite FDM filament has potential for possible applications as rapid tooling. Singh et al 21 worked with Al 2 O 3 and SiC-reinforced recycled HDPE. A sacrificial pattern (SP) for investment casting were made by 3D printing (using fused deposition modelling (FDM) machine) from rHDPE blended with Al 2 O 3 and SiC particles in various proportions.…”
Section: Introductionmentioning
confidence: 99%